Production method of aluminum-silicon-iron alloy with silicon iron as framework and silicon iron easy to separate
By using ferrosilicon as the framework in the production of aluminum-ferrosilicon alloys, the ferrosilicon is easy to separate, and using gradient cooling technology to form a controllable silicon phase and iron interwoven skeleton structure, the aluminum in the aluminum silicon raw material in the prior art is solved. The problem of difficulty in separation from silicon has achieved efficient separation and purification of silicon and iron phases.
Patent Information
- Application Number
- CN202310976724.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-04
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing industrial silicon smelting technology has problems such as difficult furnace conditions, low raw material utilization rate, high production cost, high power consumption, difficult product quality and environmental pollution, and aluminum such as clay, blue crystal, fly ash and gangue It is difficult to separate aluminum and silicon in the silicon raw materials, and it is difficult to use it to produce aluminum-silicon products.
Using a ferrosilicon alloy production method with ferrosilicon as the framework and ferrosilicon is easy to separate. By crushing and mixing silicon aluminum raw materials and carbonaceous reducing agent, adding binder and water, making a group, drying and drying Reduction reaction is carried out in an arc furnace, and then melt cooling is carried out under controlled gradient cooling conditions to form a skeleton structure with silicon phase and iron interwoven.
The structural improvement of aluminum-ferrosilicon alloy is achieved, so that it can form a controllable silicon phase and iron interwoven skeleton structure such as size and morphology, improve the efficiency of subsequent purification, promote the separation of silicon and iron phases, and obtain high added value. elemental silicon and iron-rich phase products.
Smart Images

Figure CN119433195A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of smelting, and in particular relates to a production method of an aluminum-silicon-iron alloy with ferrosilicon as a skeleton and easily separable ferrosilicon. Background Art
[0002] Aluminum is an important basic material for traditional industries. With the vigorous development of modern industry, modern science and new technologies, silicon and silicon-containing materials have become increasingly important basic materials, and their applications have been popularized in various modern industrial fields such as automobiles, ships and aviation. Bauxite is an important source of aluminum in modern industry. However, my country's bauxite resources are small, and the supply of bauxite has been unable to meet domestic demand for a long time. According to statistics, in the distribution of global bauxite resource reserves in 2021, China's bauxite reserves accounted for only 3.13% of the world. my country's bauxite production has begun to show a downward trend since 2017. According to statistics, my country's bauxite production in 2021 was 85 million tons, a year-on-year decrease of 8.3%. In addition, although my country is rich in silicon ore resources, with the rapid development of the industrial silicon industry and the need for environmental protection, the available resources have also been sharply reduced. Industrial silicon is mainly produced by electrothermal reduction, that is, silica and carbon reducing agent are crushed to a certain particle size, mixed and put into mineral heat for smelting, wherein the reducing agent used is mainly wood blocks, and a certain amount of petroleum coke and washed coal are added. The furnace conditions in the production process of this method are prone to fluctuations and difficult to control, and the raw material utilization rate is low, the production cost is high, the power consumption is high, the product quality is difficult to improve, the smoke and dust emissions are large, and the impact on the surrounding environment is large. In addition, wood blocks need to be added during the smelting process, which will consume a large amount of forest resources and cause damage to the ecological environment.
[0003] Therefore, it is of great economic significance to find alternative aluminum silicon raw material resources. In fact, my country has many types of aluminum silicon raw materials and rich reserves. In addition to bauxite, clay, kyanite, fly ash, coal gangue, etc. are all aluminum silicon raw materials with high aluminum silicon content, especially fly ash and coal gangue. Because the aluminum and silicon in them are difficult to separate, they are usually difficult to be used to produce aluminum silicon products. Chinese patent CN202011267925.4 provides a method for preparing aluminum silicon iron alloy using high aluminum fly ash and graded purification. Chinese patent CN202011267903.8 provides a method for preparing aluminum silicon iron alloy using high aluminum coal gangue and graded purification. Both patent documents mention a method for preparing a primary aluminum silicon iron alloy block. The aluminum silicon iron alloy block prepared by this method can be used for subsequent purification to prepare aluminum silicon alloy for casting, aluminum silicon iron alloy for deoxidizer and industrial silicon, etc.
[0004] The present invention attempts to improve the method for preparing Al-Si-Fe alloy on this basis, so as to obtain an Al-Si-Fe alloy that is more conducive to subsequent purification. Summary of the invention
[0005] The purpose of the present invention is to improve the structure of aluminum-silicon-iron alloy so that it forms a silicon phase and iron phase interwoven skeleton structure with controllable size and morphology. The technical solution adopted by the present invention to solve the technical problem is:
[0006] A method for producing an aluminum-silicon-iron alloy with ferrosilicon as a skeleton and easily separable ferrosilicon, comprising the following steps:
[0007] (1) crushing the silicon-aluminum raw material and the carbonaceous reducing agent, adding a binder and water to mix them evenly, forming agglomerates, drying to obtain dry agglomerates, and then putting them into an electric arc furnace for reduction reaction to obtain a single-element aluminum-ferrosilicon melt;
[0008] (2) Under controlled cooling conditions, the obtained aluminum-silicon-iron melt is subjected to gradient cooling, wherein the gradient cooling includes the following stages: in the first stage, the temperature is reduced to 800-1300°C at a cooling rate of 1-20°C / min and kept at this temperature for 10-200min; in the second stage, the temperature is reduced to 650-1000°C at a cooling rate of 0.1-20°C / min and kept at this temperature for 10-200min; in the third stage, the temperature is reduced to 600-850°C at a cooling rate of 0.1-20°C / min and kept at this temperature for 10-200min; in the fourth stage, the temperature is reduced to 577-650°C at a cooling rate of 0.1-20°C / min and kept at this temperature for 0-200min; and then naturally cooled to room temperature to obtain an aluminum-silicon-iron alloy with ferrosilicon as the skeleton and easily separable ferrosilicon.
[0009] After the silicon-aluminum raw material and the carbonaceous reducing agent in step (1) are added together, the ratio of aluminum, silicon and iron is as follows: the aluminum content is 10-88.3wt.%, the silicon content is 11.7-90wt.%, the iron content is 0.01-26.0wt.%, and the iron content is ≤(45.64-0.52Al)wt.% and ≤(40.63-0.41Si)wt.%.
[0010] Preferably, the gradient cooling in step (2) comprises: in the first stage, cooling the temperature to 850-1150°C at a cooling rate of 5-15°C / min and keeping the temperature for 20-60min; in the second stage, cooling the temperature to 700-900°C at a cooling rate of 0.5-10°C / min and keeping the temperature for 20-60min; in the third stage, cooling the temperature to 600-750°C at a cooling rate of 0.5-10°C / min and keeping the temperature for 20-60min; in the fourth stage, cooling the temperature to 577-650°C at a cooling rate of 0.5-10°C / min and keeping the temperature for 20-60min.
[0011] In the above method, the silicon-alumina raw material in step (1) can be one or a mixture of natural silicon-alumina minerals, solid waste containing silicon-alumina, or artificially synthesized silicon-alumina raw materials, wherein the natural silicon-alumina minerals include bauxite, kaolinite, albite, potassium feldspar, etc., and the solid waste containing silicon-alumina includes bauxite flotation tailings, coal gangue, fly ash, shale slag, etc.
[0012] In the above method, the carbonaceous reducing agent in step (1) includes coal, petroleum coke, calcined anthracite, coke, metallurgical coke, one of which or a mixture of several thereof.
[0013] In the above method, the amount of the carbonaceous reducing agent in step (1) is 90-95% of the required reducing agent. If it exceeds 95%, the metal carbides (especially aluminum carbide) in the alloy will increase, which will not only reduce the alloy yield but also affect the stability of arc furnace smelting.
[0014] In the above method, the mass of the binder added in step (1) is 5-10% of the mixed material, the pelletizing pressure is 50-150 MPa, the pellet drying temperature is 150-200°C, and the moisture content of the pellets after drying is not more than 1%.
[0015] In the above method, the reduction reaction temperature in the electric arc furnace in step (1) is 2200-2500°C.
[0016] In the above method, the interwoven skeleton structure described in step (2) is a skeleton structure constructed by silicon grains and iron phase grains, which still retains the macroscopic structure of the aluminum-silicon-iron alloy described in step (1) to a certain extent in appearance after centrifugal treatment, but is loose and porous inside; the gaps in the skeleton structure are filled with aluminum-silicon alloy similar to a binder.
[0017] In the above method, the silicon phase in the interwoven skeleton structure is mainly composed of silicon element.
[0018] In the above method, the Fe mass content of the iron phase in the interwoven skeleton structure is 9.7-65%, the Al mass content is 10-68%, and the Si mass content is 12-30%.
[0019] In the above method, the physical composition of the iron phase in the interwoven skeleton structure is mainly one or more of Al4FeSi, Al3FeSi2, Al2Fe5Si5, Al9Fe5Si5, and Al3Fe3Si2.
[0020] The cooling mechanism of the present invention is:
[0021] When the melt is cooled, solidification phases gradually precipitate from the material, and the following steps are performed:
[0022] L→Si
[0023] L→Si+Al3FeSi2
[0024] L+Al3FeSi2→Al4FeSi+Si
[0025] L→Al+Si+Al4FeSi
[0026] First, in the primary crystallization zone of silicon, when the melt begins to cool down, the elemental Si phase will precipitate first as the temperature continues to drop; then, after entering the iron-rich phase zone, Al3FeSi2 also begins to precipitate; when the temperature continues to drop, there will be a melting process, that is, the phase and the remaining liquid phase melt to form Al4FeSi phase and elemental silicon; finally, when the temperature reaches the low eutectic point temperature of the system, the liquid phase will completely solidify and precipitate as elemental aluminum, elemental silicon and Al4FeSi phase.
[0027] According to the ratio of aluminum, silicon and iron elements in the raw materials, the cooling and condensation process is different. In particular, when the melt cooling mechanism is precisely controlled, the grain size of each solidified phase can be effectively controlled, so that the silicon phase and iron-rich phase with larger grain size can be obtained after full growth, which provides the possibility for the effective separation of the subsequent silicon phase and iron phase. At the same time, by adjusting the holding time and cooling rate of each temperature zone, the content ratio of the iron-rich phase Al3FeSi2 and Al4FeSi phase can be effectively adjusted to increase the content of the iron-rich phase Al3FeSi2 in the final solid phase. Due to the obvious difference in the morphology of the iron-rich phase Al3FeSi2 and Al4FeSi grains, the Al3FeSi2 phase is more likely to grow into coarse grains, while the opposite phase Al4FeSi phase tends to grow into fine needles. Needle-shaped grains are very easy to break into smaller particles during the subsequent separation of silicon phase and iron phase, which makes it impossible to separate the two phases through the density difference between the iron phase and the silicon phase, and it is impossible to effectively obtain high value-added single silicon products. However, when the iron-rich phase Al3FeSi2 is dominant in the product, phase separation can be effectively achieved by controlling the large-particle iron-rich phase and silicon phase and utilizing the density difference between the two phases.
[0028] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0029] 1. During the cooling and crystallization process of the aluminum-silicon-iron melt, the silicon phase precipitates and grows at high temperature; as the temperature decreases, the iron phase begins to precipitate and interweaves with the silicon phase to form a unique skeleton structure; as the temperature continues to drop, the remaining aluminum-silicon alloy melt solidifies and exists in the skeleton gaps formed by the silicon phase and the iron phase to form a solid block;
[0030] 2. In the process of forming the interwoven framework of silicon phase and iron phase, the aluminum silicon iron melt is gradually cooled or kept warm by precisely controlling the cooling mechanism, so as to control the size, morphology, phase composition and element composition of the crystal morphology of silicon phase and iron phase and the internal organizational structure of the alloy;
[0031] 3. During the cooling process of the aluminum-silicon-ferrosilicon melt, the silicon phase first precipitates at high temperature. By controlling the cooling rate, insulation temperature and time, the silicon phase gradually grows to a suitable size, which is more conducive to subsequent separation and extraction;
[0032] 4. According to the ratio of aluminum, silicon and iron in the raw materials, a suitable temperature zone is selected for heat preservation or gradient cooling, and the appropriate heat preservation time and cooling rate are matched to effectively realize the regulation of the phase composition of the iron phase. The precipitated iron phase can be one or more of Al4FeSi, Al3FeSi2, Al2Fe5Si5, Al9Fe5Si5, and Al3Fe3Si2; and through the adjustment of the cooling process, the particle size and growth morphology of the iron phase can be effectively regulated during the transformation of different crystal phases, providing favorable conditions for the subsequent separation of silicon phase and iron phase;
[0033] 5. After strict temperature reduction control, the iron phase can grow into large-sized grains, and effectively improve the previous needle-shaped growth orientation, making it possible to separate silicon and iron. Combined with the density difference between the silicon phase and the iron phase, polysilicon products and iron-rich phase products can be obtained by gravity separation methods such as cyclone troughs and shaking tables. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a micrograph of the silicon phase and iron phase skeleton structure formed in Example 1.
[0035] Figure 2 This is the EDS analysis result of the iron phase in the skeleton of Example 1.
[0036] Figure 3 This is a micrograph of the silicon phase and iron phase skeleton structure formed in Example 2.
[0037] Figure 4 This is a micrograph of the silicon phase and iron phase skeleton structure formed in Example 3.
[0038] Figure 5 This is a micrograph of the silicon phase and iron phase skeleton structure formed in Example 4.
[0039] Figure 6 This is a micrograph of the silicon phase and iron phase skeleton structure formed in Example 5.
[0040] Figure 7 This is a micrograph of the silicon phase and iron phase skeleton structure formed in Comparative Example 1. DETAILED DESCRIPTION
[0041] The following is a detailed description of an embodiment of the present invention: This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.
[0042] Example 1
[0043] The gangue and coal crushed to a particle size less than 100 mesh are uniformly mixed in a mass ratio of 1:0.71 to form a mixed material, wherein the mass fraction of Al2O3 in the gangue is 43.78%, the mass fraction of SiO2 is 50.15%, and the mass fraction of Fe2O3 is 1.69%, and the mass fraction of Al2O3 in the coal is 46.01%, the mass fraction of SiO2 is 45.10%, and the mass fraction of Fe2O3 is 4.75%. Then, 6% of the mass of the mixed material is added with a sulfite pulp binder and 10% of water to mix the materials. Then, the mixed materials are made into pellets in a pelletizing machine at a pelletizing pressure of 100MPa, dry and dehydrate the prepared pellets at 120℃ to obtain dry lumps, with the moisture content not exceeding 1%, and then put the dry lumps into an electric arc furnace for reduction reaction, with a smelting temperature of 2200-2500℃. When the molten aluminum silicon iron alloy melt is cooled to 1400℃, it is cast in a mold and placed in a tunnel kiln for gradient temperature control, cooling to 1000℃ at 10℃ / min; keeping at 1000℃ for 30min; cooling to 800℃ at 1.5℃ / min; cooling to 700℃ at 10℃ / min; keeping at 700℃ for 30min; cooling to 580℃ at 2℃ / min. At this time, a skeleton structure composed of large flaky silicon phases and coarse granular iron phases has been formed inside the sample, such as Figure 1 At this time, according to the EDS analysis results, the phase composition of the iron phase in the skeleton is mainly Al3FeSi2 phase, with a small amount of other phases coexisting, and the overall iron phase morphology is coarse-grained, as shown in Figure 2 The melt is further cooled to room temperature to obtain an aluminum-silicon-iron alloy block, in which the mass fraction of Al is 51.63%, the mass fraction of Si is 43.31%, and the mass fraction of Fe is 5.05%.
[0044] Example 2
[0045] The gangue and coal crushed to a particle size less than 100 mesh are uniformly mixed in a mass ratio of 1:0.71 to form a mixed material, wherein the mass fraction of Al2O3 in the gangue is 42.96%, the mass fraction of SiO2 is 51.07%, and the mass fraction of Fe2O3 is 1.54%, and the mass fraction of Al2O3 in the coal is 46.01%, the mass fraction of SiO2 is 45.10%, and the mass fraction of Fe2O3 is 4.75%. Then, 6% of the mass of the mixed material is added with a sulfite pulp binder and 10% of water to mix the materials. Then, the mixed materials are made into pellets in a pelletizing machine to make pellets. The pellet pressure is 100MPa. The prepared pellets are dried and dehydrated at 120℃ to obtain dry lumps. The moisture content is required to be no more than 1%. The dry lumps are then placed in an electric arc furnace for reduction reaction. The smelting temperature is 2200-2500℃. The obtained aluminum silicon iron alloy melt is cast in a mold when the melt is cooled to 1400℃. It is placed in a tunnel kiln for gradient temperature control. The gradient temperature control is carried out, cooling to 900℃ at 10℃ / min; keeping at 900℃ for 30min; cooling to 720℃ at 1.5℃ / min; cooling to 600℃ at 10℃ / min; keeping at 600℃ for 30min. At this time, a skeleton structure composed of large flaky silicon phases and coarse granular iron phases has been formed inside the sample, such as Figure 3 After naturally cooling to room temperature, an aluminum-silicon-iron alloy block was obtained, in which the mass fraction of Al was 51.05%, the mass fraction of Si was 44.06%, and the mass fraction of Fe was 4.89%.
[0046] Example 3
[0047] The gangue and coal crushed to a particle size less than 100 mesh are uniformly mixed in a mass ratio of 1:0.75 to form a mixed material, wherein the mass fraction of Al2O3 in the gangue is 43.25%, the mass fraction of SiO2 is 47.56%, and the mass fraction of Fe2O3 is 4.45%, and the mass fraction of Al2O3 in the coal is 46.01%, the mass fraction of SiO2 is 45.10%, and the mass fraction of Fe2O3 is 4.75%. Then, 6% of the mass of the mixed material is added with a sulfite pulp binder and 10% of water to mix the mixed material, and then the mixed material is made into a briquette machine. The pellets are formed at a pressure of 100 MPa. The prepared pellets are dried and dehydrated at 120°C to obtain dry lumps, with a moisture content of no more than 1%. The dry lumps are then placed in an electric arc furnace for reduction reaction at a smelting temperature of 2200-2500°C. When the molten aluminum silicon iron alloy is cooled to 1400°C, it is cast in a mold and placed in a tunnel kiln for gradient temperature control, cooling to 950°C at 10°C / min; keeping at 950°C for 30 minutes; cooling to 850°C at 1°C / min; keeping at 850°C for 30 minutes; cooling to 580°C at 2°C / min. At this time, a skeleton structure composed of large flaky silicon phases and coarse granular iron phases has been formed inside the sample, such as Figure 4 As shown. At this time, the phase composition of the iron phase in the skeleton is mainly Al3FeSi2 phase, with a small amount of other phases coexisting, and the overall iron phase morphology is coarse-grained. The melt is further cooled to room temperature to obtain an aluminum-silicon-iron alloy block, in which the mass fraction of Al is 50.03%, the mass fraction of Si is 41.94%, and the mass fraction of Fe is 8.03%.
[0048] Example 4
[0049] The gangue and coal crushed to a particle size less than 100 mesh are uniformly mixed in a mass ratio of 1:0.79 to form a mixed material, wherein the mass fraction of Al2O3 in the gangue is 40.35%, the mass fraction of SiO2 is 45.89%, and the mass fraction of Fe2O3 is 8.22%, and the mass fraction of Al2O3 in the coal is 46.01%, the mass fraction of SiO2 is 45.10%, and the mass fraction of Fe2O3 is 4.75%. Then, 6% of the mass of the mixed material is added with sulfite pulp binder and 10% of water to mix the mixed material, and then the mixed material is placed in a briquetting machine. The pellets are made at a pressure of 100MPa. The prepared pellets are dried and dehydrated at 120°C to obtain dry lumps with a moisture content of no more than 1%. The dry lumps are then placed in an electric arc furnace for reduction reaction at a smelting temperature of 2200-2500°C. When the molten aluminum silicon iron alloy is cooled to 1400°C, it is cast in a mold and placed in a tunnel kiln for gradient temperature control. The gradient temperature control is carried out, cooling to 950°C at 10°C / min; cooling to 850°C at 1°C / min; cooling to 800°C at 10°C / min; and cooling to 580°C at 2°C / min. At this time, a skeleton structure composed of large flaky silicon phases and coarse granular iron phases has been formed inside the sample, such as Figure 5 As shown. At this time, the phase composition of the iron phase in the skeleton is mainly Al3FeSi2 phase, with a small amount of other phases coexisting, and the overall iron phase morphology is coarse-grained. The melt is further cooled to room temperature to obtain an aluminum-silicon-iron alloy block, in which the mass fraction of Al is 47.86%, the mass fraction of Si is 40.11%, and the mass fraction of Fe is 12.13%.
[0050] Example 5
[0051] The gangue and coal crushed to a particle size less than 100 mesh are uniformly mixed in a mass ratio of 1:0.80 to form a mixed material, wherein the mass fraction of Al2O3 in the gangue is 41.13%, the mass fraction of SiO2 is 46.25%, and the mass fraction of Fe2O3 is 8.35%, and the mass fraction of Al2O3 in the coal is 46.01%, the mass fraction of SiO2 is 45.10%, and the mass fraction of Fe2O3 is 4.75%. Then, 6% of the mass of the mixed material is added with a sulfite pulp binder and 10% of water to mix the materials. Then, the mixed materials are made into pellets in a pelletizing machine to make pellets. The pressure is 100MPa, and the prepared pellets are dried and dehydrated at 120℃ to obtain dry lumps, with the moisture content not exceeding 1%. The dry lumps are then placed in an electric arc furnace for reduction reaction, with a smelting temperature of 2200-2500℃. The obtained aluminum silicon iron alloy melt is cast in a mold when the melt is cooled to 1400℃, and placed in a tunnel kiln for gradient temperature control. The gradient temperature control is carried out, cooling to 1200℃ at 10℃ / min; cooling to 950℃ at 1℃ / min; cooling to 950℃ at 10℃ / min; keeping at 800℃ for 30min; cooling to 650℃ at 2℃ / min. At this time, a skeleton structure composed of large flaky silicon phases and coarse granular iron phases has been formed inside the sample, such as Figure 6 The melt is further cooled to room temperature to obtain an aluminum-silicon-iron alloy block, in which the mass fraction of Al is 48.06%, the mass fraction of Si is 39.97%, and the mass fraction of Fe is 11.97%.
[0052] Comparative Example 1
[0053] The gangue and coal crushed to a particle size less than 100 mesh are uniformly mixed in a mass ratio of 1:0.72 to form a mixed material. 1 t of gangue and coal are crushed to a particle size less than 100 mesh and uniformly mixed to form a mixed material, wherein the mass fraction of Al2O3 in the gangue component is 43.25%, the mass fraction of SiO2 is 50.86%, and the mass fraction of Fe2O3 is 1.52%, and the mass fraction of Al2O3 in the coal component is 46.01%, the mass fraction of SiO2 is 45.10%, and the mass fraction of Fe2O3 is 4.75%, and then the mixed material is added in sequence. 6% sulfite pulp binder and 10% water are mixed, and then the mixed material is made into pellets in a pelletizing machine with a pelletizing pressure of 100MPa. The prepared pellets are dried and dehydrated at 120°C to obtain dry pellets with a moisture content of no more than 1%. The dry pellets are then placed in an electric arc furnace for smelting at a smelting temperature of 2200-2500°C. When the molten aluminum silicon iron alloy melt is cooled to 1400°C, it is cast in a mold and placed in a tunnel kiln for cooling, cooling to 650°C at 5°C / min and keeping warm for 60 minutes. At this time, the internal structure of the sample is as follows: Figure 7As shown, it can be seen that the size of the iron phase and the silicon phase is significantly smaller than the skeleton grain size in Examples 1 to 5. The melt is further cooled to room temperature to obtain an aluminum-silicon-iron alloy block, in which the mass fraction of Al is 51.35%, the mass fraction of Si is 43.89%, and the mass fraction of Fe is 4.76%.
[0054] Based on the above-mentioned Examples 1-5 and Comparative Example 1, it can be seen that when the temperature reduction process is implemented on the melt after reduction, the grain size of the silicon phase and the iron phase in the sample increases significantly, and the iron phase in the comparative example is mainly needle-shaped, which is not conducive to the implementation of the subsequent gravity separation process; while the iron phase grains in the example are coarse-grained, which is convenient for subsequent gravity separation.
Claims
1. A method for producing aluminum-silicon-iron alloy with ferrosilicon as the skeleton and easy-to-separate ferrosilicon, characterized in that: The steps include: (1) crushing the silicon-aluminum raw material and the carbonaceous reducing agent, adding a binder and water to mix them evenly, forming agglomerates, drying to obtain dry agglomerates, and then putting them into an electric arc furnace for reduction reaction to obtain a single-element aluminum-ferrosilicon melt; (2) Under controlled cooling conditions, the obtained aluminum-silicon-iron melt is subjected to gradient cooling, wherein the gradient cooling includes the following stages: in the first stage, the temperature is reduced to 800-1300°C at a cooling rate of 1-20°C / min and kept at this temperature for 10-200min; in the second stage, the temperature is reduced to 650-1000°C at a cooling rate of 0.1-20°C / min and kept at this temperature for 10-200min; in the third stage, the temperature is reduced to 600-850°C at a cooling rate of 0.1-20°C / min and kept at this temperature for 10-200min; in the fourth stage, the temperature is reduced to 570-650°C at a cooling rate of 0.1-20°C / min and kept at this temperature for 0-200min; and then the temperature is naturally cooled to room temperature to obtain an aluminum-silicon-iron alloy with ferrosilicon as the skeleton and easily separable ferrosilicon.
2. The method for producing an aluminum-silicon-iron alloy with ferrosilicon as a skeleton and easily separable ferrosilicon according to claim 1, characterized in that: After the silicon-aluminum raw material and the carbonaceous reducing agent in step (1) are added together, the ratio of aluminum, silicon and iron is as follows: the aluminum content is 10-88.3wt.%, the silicon content is 11.7-90wt.%, the iron content is 0.01-26.0wt.%, and the iron content is ≤(45.64-0.52Al)wt.% and ≤(40.63-0.41Si)wt.%.
3. The method for producing an aluminum-silicon-iron alloy with ferrosilicon as a skeleton and easily separable ferrosilicon according to claim 1, characterized in that: The gradient cooling in step (2) includes: in the first stage, the temperature is lowered to 850-1150°C at a cooling rate of 5-15°C / min and kept warm for 20-60min; in the second stage, the temperature is lowered to 700-900°C at a cooling rate of 0.5-10°C / min and kept warm for 20-60min; in the third stage, the temperature is lowered to 600-750°C at a cooling rate of 0.5-10°C / min and kept warm for 20-60min; in the fourth stage, the temperature is lowered to 577-650°C at a cooling rate of 0.5-10°C / min and kept warm for 20-60min.
Citation Information
Patent Citations
Method for preparing aluminum-silicon-iron alloy from high-aluminum coal gangue and conducting graded purification
CN113913621A
A method for preparing aluminum-silicon-iron alloy using high-aluminum fly ash and grading purification
CN114480855B